Disrupsi Politik: Peluang dan Tantangan Partai Politik Baru Jelang Pemilu 2024 - Fitria Barokah; Tabah Maryanah; Ari Darmastuti; Hertanto Hertanto (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2022)
In 2024, there will be a grand election based on the decision of the Indonesian KPU No. 21 of 2022, there are six newcomer parties that have already pocketed a ratification decree from the Legal Entity and the Ministry of Law and Human Rights and are ready to develop a strategy to participate in the contestation. This article discusses the opportunities and challenges of the emergence of new parties faced in the era of disruption by utilizing information technology in facing the 2024 election competition. The writing method uses a literature review and data that will be obtained through literature studies, such as books, scientific journals, websites, and other things. Things that are relevant to the problem under study. The results and analysis in this paper indicate that the presence of a new party in the upcoming 2024 elections will be political years that are on the verge of vulnerability and division, while a powerful strategy to minimize divisions is to instill an internal party democracy system, so that internal conflicts between members in the party does not happen again. Another challenge is that disruption will hijack the role of political parties if political parties are reluctant to follow the flow of disruption. In the era of disruption, the emergence of political parties provides opportunities for mass mobilization during campaigns using social media which is considered more effective and has a broad and equitable reach. In addition, disruption can be used by political parties for party branding strategies. However, the bad impact of this disruption can lead to social media wars between political parties on various social media pages such as the spread of hoax news.